Analisis Pantai Lombang Kabupaten Sumenep Menjadi Destinasi Wisata Halal - Faraby, Muhammad Ersya; Rahman, Taufiqur (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This study aims to determine the analysis of the potential and challenges of Lombang beach Sumenep Regency to become a halal tourist destination. Halal tourism is tourism in which natural, cultural, or artificial origin is framed by Islamic values where activities are supported by various facilities and services (hotels, restaurants, travel agencies, spas) provided by the community, entrepreneurs, government, and local governments that meet sharia / Islamic provisions. In this research, researchers will conduct a research as a step to find out the potential and challenges related to the availability of infrastructure, community acceptance, and social facts of Lombang beach to become a halal tourist destination. Then the researcher will describe the indicators of halal tourism, then mapping Attractions, amenities, accessibility, ancillary. This study uses descriptive qualitative approach with case study method. Technically, researchers will map informants consisting of the Sumenep Regency Tourism, Culture, Youth and Sports Office, tourist attraction managers, tourists, and communities around Lombang beach. Basically, the results showed that the Lombang beach of Sumenep Regency deserves to be a halal tourist destination by looking at the existing tourism potential. In addition, there must be a synergy between the Sumenep Regency local government, tourism managers, and local communities around the Lombang beach to unite perceptions in supporting halal tourist destinations. Keywords: Halal Tourism, Lombang Beach, Sumenep Madura